2007
DOI: 10.1104/pp.107.100404
|View full text |Cite
|
Sign up to set email alerts
|

Mutation ofE1-CONJUGATING ENZYME-RELATED1Decreases RELATED TO UBIQUITIN Conjugation and Alters Auxin Response and Development

Abstract: The ubiquitin-like protein RELATED TO UBIQUITIN (RUB) is conjugated to CULLIN (CUL) proteins to modulate the activity of Skp1-Cullin-F-box (SCF) ubiquitylation complexes. RUB conjugation to specific target proteins is necessary for the development of many organisms, including Arabidopsis (Arabidopsis thaliana). Here, we report the isolation and characterization of e1-conjugating enzyme-related1-1 (ecr1-1), an Arabidopsis mutant compromised in RUB conjugation. The ecr1-1 mutation causes a missense change locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…The even stronger decrease in hypocotyl elongation together with the visible increase in anthocyanin accumulation suggested that axr1 as well ecr1 mutants are already sensitized in this pathway (Fig. 4, A and B; Leyser et al, 1993;Woodward et al, 2007). We then also found that HY5 protein but not HY5 transcript level increases in dark-grown MLN4924-treated seedlings and that this correlates with an increase in transcript abundance of light-induced genes in these seedlings (Fig.…”
Section: Mln4924 Inhibits the Function Of Other Crlssupporting
confidence: 53%
See 1 more Smart Citation
“…The even stronger decrease in hypocotyl elongation together with the visible increase in anthocyanin accumulation suggested that axr1 as well ecr1 mutants are already sensitized in this pathway (Fig. 4, A and B; Leyser et al, 1993;Woodward et al, 2007). We then also found that HY5 protein but not HY5 transcript level increases in dark-grown MLN4924-treated seedlings and that this correlates with an increase in transcript abundance of light-induced genes in these seedlings (Fig.…”
Section: Mln4924 Inhibits the Function Of Other Crlssupporting
confidence: 53%
“…In Arabidopsis, NEDD8 is known as RUB and is encoded by three different genes (Bostick et al, 2004); NAE is composed of the NAE1 subunit AXR1 or its homolog AXR1-LIKE (AXL) and the UBA3 subunit E1 C-TERMINAL RELATED (ECR1; del Pozo et al, 2002;Dharmasiri et al, 2007). axr1 and ecr1 mutants are insensitive to the root growth-inhibiting effect of the phytohormone auxin and have reduced root gravitropism (Leyser et al, 1993;Woodward et al, 2007). axr1 mutants are partially impaired in NEDD8 conjugation, and the effect of the axr1 mutation on NEDD8 conjugation and development is enhanced when the AXR1 homolog AXL is dysfunctional, resulting in embryo lethality (Dharmasiri et al, 2007;Hotton et al, 2011).…”
mentioning
confidence: 99%
“…Like ubiquitin, NEDD8 is conjugated to substrate proteins through an enzymatic cascade that includes the E1 NEDD8 activating enzyme (NAE); in Arabidopsis, NAE is a heterodimer of AXR1 (AUXIN RESISTANT1) or AXL (AXR1-LIKE) and ECR1 (E1 C-TERMINAL RELATED1). The NEDD8-conjugating cascade also includes an E2 conjugating enzyme; in Arabidopsis, this is RUB1 CONJUGATING ENZYME1 (RCE1; Pozo et al, 1998;del Pozo and Estelle, 1999;del Pozo et al, 2002;Dharmasiri et al, 2007;Woodward et al, 2007). NEDD8 is ultimately conjugated to its protein substrate with the help of E3 NEDD8 ligases like RBX1 (RING BOX1), a constitutive subunit of cullin-RING E3 ubiquitin ligases (CRLs), and DEFECTIVE IN CULLIN NEDDYLATION (DCN; Gray et al, 2002;Duda et al, 2008;Kurz et al, 2008).…”
Section: Nedd8 (Neural Precursor Cell Expressed De-velopmentally Dowmentioning
confidence: 99%
“…In many cases, slowed degradation of the mutant protein was experimentally verified (Timpte et al 1994;Leyser et al 1996;Rouse et al 1998;Nagpal et al 2000;Tian et al 2002;Tatematsu et al 2004;Yang et al 2004). Other auxin response mutants include plants with defective subunits of the SCF ubiquitin E3 ligase or mutations that cause misregulation of SCF activity/ assembly (Ruegger et al 1998;Gray et al 2003;Hellmann et al 2003;Cheng et al 2004;Chuang et al 2004;Feng et al 2004;Dharmasiri et al 2005b;Quint et al 2005;Alonso-Peral et al 2006;Walsh et al 2006;Moon et al 2007;Woodward et al 2007).…”
mentioning
confidence: 99%
“…This attachment follows an enzymatic cascade similar to that of ubiquitin, beginning with RUB1/2 activation by a heterodimeric E1, then transfer to the RUB1/2 E2, and finally transfer to CUL1 using RBX1 as part of the RUB1/2 E3 (Del Pozo et al 1998Kamura et al 1999;Gray et al 2002;Bostick et al 2004;Larsen and Cancel 2004;Woodward et al 2007). One of the original auxin resistant mutants, axr1, is an allele of the N-terminal half of the RUB1/2 E1 heterodimer (Leyser et al 1993;Del Pozo et al 1998).…”
mentioning
confidence: 99%